2002
DOI: 10.1126/science.1067766
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Induction of BDNF-Mediated Long-Term Potentiation

Abstract: Brain-derived neurotrophic factor (BDNF) and other neurotrophins are critically involved in long-term potentiation (LTP). Previous reports point to a presynaptic site of neurotrophin action. By imaging dentate granule cells in mouse hippocampal slices, we identified BDNF-evoked Ca2+ transients in dendrites and spines, but not at presynaptic sites. Pairing a weak burst of synaptic stimulation with a brief dendritic BDNF application caused an immediate and robust induction of LTP. LTP induction required activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
257
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(272 citation statements)
references
References 38 publications
15
257
0
Order By: Relevance
“…However, in this study no experiments were performed to analyze the response in mice lacking presynaptic TrkB receptors and therefore the authors concluded that BDNF would target presynaptic TrkB receptors to induce synaptic potentiation. In contrast with the reports suggesting a concurrent role of pre-and post-synaptic TrkB receptors in LTP in the CA1 region of the hippocampus, a postsynaptic effect was proposed to account for the robust induction of LTP at the synapses of the medial perforant path fibers when BDNF was applied together with a weak synaptic stimulation that would not normally induce synaptic potentiation (Kovalchuk et al, 2002). Although a presynaptic effect of BDNF was not ruled out in this paradigm, the differences may be due to the distinct synapses investigated.…”
Section: Bdnf and Ltp In The Hippocampusmentioning
confidence: 47%
See 1 more Smart Citation
“…However, in this study no experiments were performed to analyze the response in mice lacking presynaptic TrkB receptors and therefore the authors concluded that BDNF would target presynaptic TrkB receptors to induce synaptic potentiation. In contrast with the reports suggesting a concurrent role of pre-and post-synaptic TrkB receptors in LTP in the CA1 region of the hippocampus, a postsynaptic effect was proposed to account for the robust induction of LTP at the synapses of the medial perforant path fibers when BDNF was applied together with a weak synaptic stimulation that would not normally induce synaptic potentiation (Kovalchuk et al, 2002). Although a presynaptic effect of BDNF was not ruled out in this paradigm, the differences may be due to the distinct synapses investigated.…”
Section: Bdnf and Ltp In The Hippocampusmentioning
confidence: 47%
“…Facilitatory effects of BDNF in the induction of LTP have also been reported under conditions of weak synaptic stimulation that would not normally induce synaptic potentiation in the hippocampal CA1 region (Kovalchuk et al, 2002). Bath application of BDNF also triggers a sustained enhancement of synaptic transmission in the CA1 region of the hippocampus by a mechanism dependent on protein synthesis (Ji et al, 2010;Kang and Schuman, 1996).…”
Section: Bdnf and Ltp In The Hippocampusmentioning
confidence: 91%
“…Additional findings that high-frequency stimulation or more natural theta patterns of afferent activity upregulates BDNF expression further corroborate its role in synaptic plasticity (Gooney and Lynch, 2001;Balkowiec and Katz, 2002). Mechanisms underlying the function of BDNF in plasticity include presynaptic (Gottschalk et al, 1998;Pozzo-Miller et al, 1999;Jovanovic et al, 2000;Xu et al, 2000;Zakharenko et al, 2003;Tyler et al, 2006) or postsynaptic actions Lin et al, 1998;Di Luca et al, 2001;Kovalchuk et al, 2002) as well as coordinate pre-and postsynaptic processes (Alder et al, 2005;Gartner et al, 2006). Despite a great deal of progress on the function of BDNF in LTP, investigation of its role in associative learning has only more recently begun to be examined.…”
Section: Introductionmentioning
confidence: 62%
“…The deficits in LTP resulting from BDNF knockdown could be rescued by addition of recombinant BDNF to medium (Patterson et al, 1996) or adenovirus-mediated overexpression of BDNF (Korte et al, 1996). Studies have also suggested that BDNF itself could induce (Messaoudi et al, 1998) or facilitate (Kovalchuk et al, 2002) LTP expression in the hippocampus. Additional findings that high-frequency stimulation or more natural theta patterns of afferent activity upregulates BDNF expression further corroborate its role in synaptic plasticity (Gooney and Lynch, 2001;Balkowiec and Katz, 2002).…”
Section: Introductionmentioning
confidence: 87%
“…A subcellular fractionation procedure was used to separate protein from the cytosolic and synaptic membrane compartments because there can also be local synthesis of BDNF in dendrites (Hartmann et al, 2001;Kovalchuk et al, 2002), where it can directly affect synaptic plasticity. Tissue was homogenized in a Tris buffer containing a cocktail of protease inhibitors (Sacktor et al, 1993).…”
Section: Hippocampal Protein Isolationmentioning
confidence: 99%